The fossil record of Ceratophrys Wied-Neuwied (Anura: Ceratophryidae): a revision and update of fossil South American horned frogs - Nicoli, Laura (Zootaxa, 2019)
Ceratophrys is the most diverse and widely distributed genus of Ceratophryidae, the clade of South American horned frogs. Numerous anuran fossil remains, including several fossil species, have been assigned to this genus. However, this seemingly extensive fossil record is problematic because several of the fossils are not properly identified and most of the taxonomic assignations are not justified. The present study traces all the fossil material attributed to Ceratophrys, clarifying, when possible, institutional allocations. Each of the remains was examined and its taxonomic assignation revisited, based on the morphology and possible synapomorphies of the genus, including its living species. Numerous fossils were properly identified and assigned with certainty to Ceratophrys. Only one fossil species, Ceratophrys ameghinorum, is considered valid. This information, along with recently reported evidence of fossil Ceratophrys, is briefly summarized to serve as a practical reference for the entire known fossil record of the genus. The fossil record is not especially informative about the evolution or distribution pattern of Ceratophrys, because most of the remains are relatively young (post-Miocene), collected within the present distribution of the genus, and morphologically consistent with that of the extant species. However, some useful information has emerged. The presence of Ceratophrys is well documented since the Neogene in the Pampean Region of South America. The single valid fossil species, Ceratophrys ameghinorum, possesses a unique combination of characters that reflects a mixture of characters observed in different clades of the genus; thus, resolution of its phylogentic position will inform our understanding of the evolution of the genus. The paleoenvironmental significance of some Ceratophrys fossils is also discussed, addressing the wide, but incompletely known current distribution and environmental tolerance of the genus.